"Do you have mowing the lawn?" – improvements in word retrieval and grammar following constraint-induced language therapy in primary progressive aphasia. Issue 3 (4th March 2017) - Hameister, Inga; Nickels, Lyndsey; Abel, Stefanie; Croot, Karen
ABSTRACT: Background : Much recent progress has been made in developing speech–language therapy in primary progressive aphasia (PPA). Several treatment approaches that have shown significant effects with people with aphasia have been adapted and re-evaluated for PPA. Constraint-induced aphasia therapy (CIAT) is a well-evaluated method that has yielded significant language improvements in people with post-stroke aphasia but has not yet been evaluated with people with PPA. Nevertheless, the combination of CIAT features like massed practice and a motivating communicative setting seem likely to make it a suitable tool for improving the speech and language performance of individuals with PPA as well. Aims : This study investigates the effectiveness of a modified CIAT protocol on word retrieval, grammatical structure and connected speech in two individuals with non-fluent variant PPA (nfvPPA). Methods and procedures : Two participants with nfvPPA took part in a 9-day intensive CIAT-based group therapy with additional computer-based home training. Stimuli were 120 photos of people performing daily life activities, which could be described using a simple (e.g., "The man is mowing the lawn") or reduced (e.g., "mowing the lawn") sentence structure. During the treatment phase, the participants were required to request picture cards from other group members using spoken language only. The task difficulty was increased hierarchically (shaped) in accordance to each participant's performance level. Outcomes and results : Directly after therapy, both participants achieved significant improvements in their noun and verb naming accuracy and their grammatical structure for trained items. Training effects were maintained 2 months after therapy. Moreover, generalisation to different pictures of the same item was found for both participants and one participant also showed improved grammatical structure when describing untrained pictures. No significant generalisation to untrained connected speech samples was observed for either participant. Conclusion : This study illustrates that CIAT can be effective in people with PPA. However, further modifications of CIAT should be considered to facilitate generalisation and in order to determine which aspects of the treatment are most important.